Neurological aspects of urinary incontinence in the elderly - Vladimir Anatolyevich Parfenov (Неврология, нейропсихиатрия, психосоматика, 2013)
The paper gives data on the prevalence, pathogenesis, and treatment of urinary incontinence in the elderly. There is a high rate of urinary incontinence among the patients who have experienced stroke or suffer from dementia or other neurological diseases. The ideas on the pathogenesis and manifestations of overactive bladder, stress urinary incontinence are outlined. Currently available drugs (anticholinergics, antidepressants, botulinum toxin preparations), methods for behavioral therapy and physiotherapy, and skin care in urinary incontinence are discussed. The current treatment options can improve quality of life in the elderly and their milieu.